A pragmatic approach to measuring physical literacy and behavioural outcomes in youth with and without disabilities. Issue 2 (3rd April 2023) - Arbour-Nicitopoulos, Kelly P.; Bremer, Emily; Leo, Jennifer; Wright, F. Virginia
ABSTRACT: This study used a pragmatic measurement approach to examine changes in physical literacy (PL) and physical activity (PA) behaviour outcomes associated with a community-based PL programme for youth with and without disabilities. A single group, pre-post study was conducted with 67 youth (68.7% male; 62.7% with a disability; 12.2 ±1.7 years) participating in a 16-week, inclusive PL programme offered across three community sites. Valid, age-appropriate outcome measures were completed at baseline and post-programme. Gains were found in movement competence (Cohen's d z = 0.99; n = 46), overall self-regulated motivation ( d z = 0.29; n = 43), confidence ( d z = 0.15 to 0.21; n = 43), and minutes spent in moderate PA behaviour ( d z = 0.83; n = 20). Peer relationships ratings (n = 35) indicated strong social support, and mean weekly attendance was 78.5% (n = 62). Findings provide evidence of gains in PL, particularly motor competence, and PA behaviour outcomes associated with PL programme participation in youth with and without disabilities.